UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPS MELALUI STRATEGI PEER LESSONS DENGAN MEDIA PERMAINAN ULAR TANGGA - Dena Julianti (Latifah Pres, 2018)
The author carried out this research was motivated by the low activity and student learning outcomes in social studies learning material socio-cultural diversity based on natural appearance. To increase student activity and learning outcomes, teachers need to design a strategy, and effective learning media to improve the learning process. One effort that can be done is to use peer lessons strategies with the snake and ladder game media. This study uses classroom action research method using Hopkins research design, which consists of plan, act, observe, and reflect. The instrument of this study consisted of student learning activeness sheets and evaluation questions. From the results of data analysis obtained, the authors conclude that the use of peer lessons strategies with snake game media can increase student activity and learning outcomes. This can be seen from the percentage of student learning activity in the first cycle 65,70% and in the second cycle increased to 85,20%. While increasing student learning outcomes can be seen from completeness in each cycle. Student learning outcomes in the first cycle reached a percentage of 66,67% or 14 students and in the second cycle reached a percentage of 90,48% or 19 students. Thus, it can be concluded that the implementation of the peer lessons strategy with the snakes and ladders game media succeeded in increasing the activeness and learning outcomes of social studies for fourth grade students of SDN Cikole, Cimalaka District, Sumedang District, 2017/2018 Academic Year.